1987
DOI: 10.1063/1.452732
|View full text |Cite
|
Sign up to set email alerts
|

High resolution lifetime measurements of the perturbed J′=0 levels of the 1B3u state of pyrazine

Abstract: The lowest excited singlet 1 B 3u state of pyrazine is known to be coupled to a number of triplet 3 B states. Using a strongly collimated molecular beam and a single frequency laser it is sh~~ that the J I = 0 of the og transition contains at least 36 states. We have individually excited eight ofthese states and studied its decay. The lifetimes found (typically 450 ns) ~o.not scale with the intensities of the excitation spectrum. This deviation is caused by a nonradlatlve decay of the zero order 3 B 3" states.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(17 citation statements)
references
References 11 publications
2
15
0
Order By: Relevance
“…Summarising, it has been shown that (a) the strength of the singlet-triplet coupling in the B 3u states is not dependent on a magnetic field, (b) the zeroorder width of the triplet states is due to purely intramolecular relaxation and does not arise solely from collisions, and (c) the zero-order width γ of the triplet states consists both of a magnetic field sensitive part (with a typical value of about 0.3 MHz at zero field) and a magnetic field insensitive part (with a typical value of about 0.7 MHz). For low J´ this width is not the dominating part of the total width for those MEs which are responsible for the vast majority of the fluorescence intensity [8]. However, in a magnetic field this may not be the case.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…Summarising, it has been shown that (a) the strength of the singlet-triplet coupling in the B 3u states is not dependent on a magnetic field, (b) the zeroorder width of the triplet states is due to purely intramolecular relaxation and does not arise solely from collisions, and (c) the zero-order width γ of the triplet states consists both of a magnetic field sensitive part (with a typical value of about 0.3 MHz at zero field) and a magnetic field insensitive part (with a typical value of about 0.7 MHz). For low J´ this width is not the dominating part of the total width for those MEs which are responsible for the vast majority of the fluorescence intensity [8]. However, in a magnetic field this may not be the case.…”
Section: Resultsmentioning
confidence: 91%
“…We then obtain 2γ 1 (H = 0) ≈ 2Γ/(3N); i.e., γ 1 (H = 0) ≈ 0.3 MHz, where we have used γ 1 (H) ≈ 3γ 1 (H = 0). Using a typical value for γ of about 1 MHz [8], we find for γ 2 about 0.7 MHz. Note that for high J´, where [6,7] Γ ME =Γ/N+γ+Γ c ≈ γ+Γ c ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations